Selection and Interpretation of Scientific Evidence in Preparation for Policy Decisions: A Case Study Regarding Introduction of Rotavirus Vaccine Into National Immunization Programs in Sweden, Norway, Finland, and Denmark - St-Martin, Gry; Lindstrand, Ann; Sandbu, Synne; Fischer, Thea Kølsen (Frontiers in Public Health, 2018)
- The World Health Organization recommends inclusion of rotavirus vaccines in national immunisation programmes worldwide. - Nordic countries are usually considered comparable in terms of demographics and healthcare services and have comparable rotavirus disease burden. - Nevertheless, the countries have reached different decisions regarding rotavirus vaccine: Norway and Finland have already introduced rotavirus vaccines into their national immunisation programmes and Sweden is currently changing its recommendation and vaccines will now be introduced on a national scale while Denmark has decided against it. - This study focuses on the selection and interpretation of medical and epidemiological evidence used during the decision-making processes in Sweden, Norway, Finland, and Denmark. - The so-called ‘severity criteria’ is identified as one of the main reasons for the different policy decisions